Modern Students are Looking for Work: Why and How to Find - Sokolova, Anna (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
In the article the results of sociological research of the phenomenon of working student (on the example of student young people of the Lugansk region) are considered. The theoretical and empiric analysis of economic activity of student young people is presented. Motivation of additional employment of both workings students is certain and those, whoever works so far, but wants it. Attention is accented on the possible ways of search by the student young people of places of additional employment, and also on its influence on intensity of educational practices of students, in particular on their academic progress. It is analysed, in which one spheres students work but whether their work coincides with the type of studies in higher educational establishment. It is marked, that actualization of economic subjective of the modern Ukrainian students is complicated not only through a financial-economic crisis in our country but also through position of employers and some personalities descriptions of future specialists.